Application of frequency criterion in designing controller for uncertain balancing robot - Nguyen, Tan Phat; Nguyen , Van Dong Hai; Nguyen , Phong Luu; Nguyen, Minh Tam; Mircea Ivanescu , (Journal of Technical Education Science, 2017)
In most nonlinear system, it is difficult to identify in a state sapce all system parameters exactly,especially after a period of working operation since system parameters usually vary. So, a system control method is very important in this case. This paper focuses on a method of designing PD controller for a balancing robot-cart. The uncertainty of model parameters was introduced as constraints in state space. PD controller was designed through choosing Lyapunov function which was transformed by Kalman-Yakubovich-Popov lemma, a basic theoretical method based on frequency criterion. After the stability of the control system had been determined by Lyapunov techniques, stability of the controller was proved by mathematics and shown by simulation results.